The Liability of The Land Deed Official (PPAT) in Terms of The Reading of The Grant Deed when Carried Out by Its Employees and The Lack of Witnesses in The Deed (Case Study of Verdict Number 3/PDT. G/2020/PN BLA) - Audita Kandi Putri Maharani; Mohamad Fajri Mekka Putra; Henny Marlina (IHSA Institute, 2022)
Conveyancer (PPAT) has the authority to make an authentic deed regarding the transfer of land rights, one of them is the Grant Deed. In making the deed, Conveyancer must be responsible for what they made because Conveyancer has been appointed directly by the Minister of Agrarian and Land Affairs. The article discusses the legal issues in the Blora District Court Decision Number 3/Pdt.G/2020/PN Bla, namely regarding Conveyancer's responsibilities based on the Grant of a Deed read by his employees and the lack of witnesses in making the Grant Deed. This study uses a normative juridical method by using secondary data sourced from primary, secondary, and tertiary legal materials. The Deed of Grant is an authentic deed that can be used as a perfect evidence. Due to its irrevocable nature and can't be erased, except for certain reasons, it requires accuracy and prudence in the preparation of the deed. Conveyancer is obliged to read out the Deed of Grant before it is signed by the parties and there must be at least 2 (two) witnesses in making the Deed of Grant in accordance with the provisions of Article 22 of Government Regulation Number 37 of 1998 concerning the Regulation of the Position of the Official Making the Land Deed which is currently updated with Government Regulation Number 24 of 2016.